Bioactive compounds from agroindustrial byproducts and their applications: From traditional methods to green technologies (Scientia Agropecuaria, 2024)
The use of agroindustrial byproducts (solids and liquids) with bioactive compounds has developed and grown remarkably. Existing methodologies and some new approaches developed through various research efforts have demonstrated their viability. The bioactive compounds commonly studied in research are phenolic compounds and carotenoids because of their potential as antioxidants and natural additives that can prolong the shelf life of certain foods. Meanwhile, conventional extraction methods are being replaced with green technologies, which offer reduced extraction time and are more environmentally friendly, among other advantages. In addition, protecting and preserving bioactive compounds from environmental conditions by applying microencapsulation and nanoencapsulation methods is crucial. These studies have shown that combining methods yields better results than using them individually. Therefore, it is recommended that unconventional methods and green technologies be integrated into future research. This approach will help determine whether acquiring them is profitable and feasible for the agroindustrial companies responsible for this waste. This review demonstrates the potential use of agricultural byproducts to obtain bioactive compounds (through combined extraction methods for improved efficiency) and incorporate them in different industries, such as food, cosmetics, and aquaculture, thereby creating a favorable socio-environmental impact by reducing soil and water pollution.